A cyber-physical system approach for model based predictive control and modeling of COVID-19 in India. Issue 1 (2nd January 2021) - Sharma, Ashish; Agarwal, Basant
Abstract: The coronavirus disease (COVID-19) pandemic has become a global health crisis due to spread of the infection all over the world. It is important to understand the transmission dynamics of this highly infectious disease to control and prevent its spread. In this paper, we propose a mathematical model along with the Model Predictive Control (MPC) for spread of coronavirus disease infection based on time and space constraints. We focus on the predictive control strategies based on step taken against this epidemic in India. The proposed model is verified using UPPAAL tool, and the analysis of the model is performed on the data related to the disease from April 1 to 18 in India.